Chronic exposure to mercury increases arrhythmia and mortality post-acute myocardial infarction in rats - Bello, Keren A. S.; Wilke, Maria Clara B.; Simões, Rakel P.; Landim-Vieira, Maicon; Langa, Paulina; Stefanon, Ivanita; Vassallo, Dalton Valentim; Fernandes, Aurélia Araújo (Frontiers in Physiology, 2023)
Mercury (Hg) is a heavy metal that causes a variety of toxic effects in eukaryotic cells. Previous studies have reported detrimental effects of mercury toxicity in the cardiovascular system. Given the importance of understanding the relationship between Hg and cardiovascular disease, we sought to investigate if the Hg could worsen the myocardial repercussions following ischemic injury. We demonstrated that once mercury toxicity is established, it can influence the outcome of myocardial infarction (MI). Male Wistar rats received intramuscular injections of either saline (NaCl 0.9%) or mercuric chloride (HgCl2, first dose of 4.6 μg/kg, and subsequent doses of 0.07 μg/kg/day) for 4 weeks. Three weeks post-exposure, we induced transmural infarction in the left ventricle free wall through coronary artery occlusion surgery. ECG recordings obtained from MI groups demonstrated alterations in the rhythm of the heartbeat/heart electrical activity, as expected, including ventricular extrasystoles and ventricular tachycardia. However, the MI group exposed to Hg (MI-Hg) exhibited augmented ventricular extrasystoles and ventricular tachycardia compared to the MI group. Also, Basckó coefficient revealed that the arrhythmic eventsafter MIwere aggravated by Hg exposure.Our results indicate that the significantly increased mortality in MI-Hg groups when compared to MI (21%, MI vs 32%, MI-Hg) is correlated with greater